EXPLORATION OF STAINED GLASS IN LAWANG SEWU AS INSPIRATION FOR EMBROIDERY MOTIFS REVERSE APPLIQUE ON VEST - I anatul Maulaya; Yuhri Inang (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
Stained Glass in Lawang Sewu is one of the stained glass ornaments found in one of Indonesia's cultural heritage buildings, Lawang Sewu. The shape of stained glass in Lawang Sewu has a beautiful and distinctive motif that is the inspiration for embroidery motifs. This study aims to determine 1) the process of exploring stained glass in Lawang Sewu as an inspiration for reverse applique embroidery motifs on vests, and 2) the results of exploration of stained glass in Lawang Sewu as inspiration for reverse applique embroidery motifs on vests. The type of research is design development research. The research method uses the Double Diamond Model including four stages: Discover, searching for and collecting information about Kaca Patri Lawang Sewu, Define, taking important priorities into one on the moodboard to create a Reverse Applique embroidery motif design on a vest, Develop, realizing the stained glass in Lawang Sewu motif in the form of reverse applique embroidery and sewing it in the form of a vest, Deliver, the final stage, namely the prototype is selected and approved, and the product is completed by testing the feasibility of the work or product is completed. The data collection instrument in the process uses an observation sheet to the Expert and is approved by the supervising lecturer. The data analysis technique uses a qualitative descriptive analysis technique using the mean or average. The results are reviewed from 5 aspects, namely the creativity and originality aspects, the embroidery motif pattern structure aspect, the color aspect, the application of techniques, and the functionality aspect. The aspect with the highest mean is the embroidery motif pattern structure aspect, with a mean of 5 (very good). While the aspect with the lowest results is the functionality aspect, which is 4.4 (very good). By getting a very good response, this product is expected to be an inspiration for exploration and innovation in the fashion world.